An Evaluation for Model Testability approaches - Nikfard, Pourya; Ibrahim, Suhaimi Bin; Rohani, Babak Darvish; Selamat, Harihodin Bin; Mahrin, Mohd Nazri (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Design for testability is a very important issue in software engineering. It becomes crucial in the case of Model Based Testing where models are generally not tested before using as input of Model Based Testing. The quality of design models (e.g.; UML models), has received less attention, which are main artifacts of any software design. Testability tends to make the validation phase more efficient in exposing faults during testing, and consequently to increase quality of the end-product to meet required specifications. Testability modeling has been researched for many years. Unfortunately, the modeling of a design for testability is often performed after the design is complete. This limits the functional use of the testability model to determining what level of test coverage is available in the design. This information may be useful to help assess whether a product meets the target requirement to achieve a desired level of test coverage, but has little proactive effect on making the design more testable.